Answer:
[tex]\implies (x-1)^2+(y-3)^2=10[/tex]
Step-by-step explanation:
End points of the diameter of the circle are:
[tex](-2,\:4) \implies x_1= -2, \: y_1= 4[/tex]
[tex](4,\:2) \implies x_2= 4, \: y_2= 2[/tex]
Equation of circle in diameter form is given as:
[tex](x-x_1)(x-x_2)+(y-y_1)(y-y_2)=0[/tex]
Plugging in the values of [tex]x_1, \: y_1,\:x_2, \: y_2[/tex] in the above equation, we find:
[tex][x-(-2)](x-4)+(y-4)(y-2)=0[/tex]
[tex]\implies (x+2)(x-4)+(y-4)(y-2)=0[/tex]
[tex]\implies x^2-2x-8+y^2-6y+8=0[/tex]
[tex]\implies x^2-2x+1-9+y^2-6y+9-1=0[/tex]
[tex]\implies (x^2-2x+1)-9+(y^2-6y+9)-1=0[/tex]
[tex]\implies (x-1)^2+(y-3)^2-10=0[/tex]
[tex]\implies (x-1)^2+(y-3)^2=10[/tex]
This is the required equation of circle in standard form.